Visual Function in Mice Lacking GM3 Synthase. (3rd June 2019) - Hiraoka, Miki; Ohkawa, Ei; Abe, Akira; Murata, Masaki; Go, Shinji; Inokuchi, Jin-ichi; Ohguro, Hiroshi
ABSTRACT: Purpose : Most complex gangliosides in vertebrates are formed from ganglioside GM3. GM3 deficiency in humans can result in epilepsy and visual impairment. To investigate whether a deficiency of GM3 is involved in visual function, ST3GAL5 −/− mice with mutations in the ST3GAL5 gene-coded GM3 synthase were employed. Materials and Methods : Sixty mice were employed in this study. The glycosphingolipids of mice retinas were analyzed through high performance thin layer chromatography. The morphology of the optic nerves and retinas were evaluated by hematoxylin and eosin staining and immunohistochemical analysis using an anti-glial fibrillary acidic protein (GFAP) antibody. An electroretinogram (ERG) was applied on the eyes of 4, 9, 12, and 14-month-old mice. Also, visual evoked potential (VEP) was applied on 13-month-old mice. Results : The GM3 in the retinas was detected in ST3GAL5 +/+ mice but not ST3GAL5 −/− mice. Also, GM1b and GD1α expressions and lactosylceramide accumulation were found in the ST3GAL5 −/− mouse retinas. There was no significant difference in GFAP expression in the retinas or optic discs between ST3GAL5 +/+ and ST3GAL5 −/− mice. Furthermore, the outcome of ERG and VEP analysis showed no disparity between the two strains in 13 and 14-month-old mice. Conclusion : In the eye, neither histopathological abnormalities nor abnormal functions of the retina were found in GM3-deficient mice. Differing from the situation in patients with GM3 deficiency, the lack of GM3 in mice did not lead to optic nerve atrophy.